2004
DOI: 10.2135/cropsci2004.1391
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Carbon Partitioning in Switchgrass

Abstract: Grasslands have an underground biomass component that serves as a carbon (C) storage sink. Switchgrass (Panicum virgatum L.) has potential as a biofuel crop. Our objectives were to determine biomass and C partitioning in aboveground and belowground plant components and changes in soil organic C in switchgrass. Cultivars Sunburst and Dacotah were field grown over 3 yr at Mandan, ND. Aboveground biomass was sampled and separated into leaves, stems, senesced, and litter biomass. Root biomass to 1.1‐m depth and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
3
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 20 publications
7
163
3
8
Order By: Relevance
“…43 Frank et al 33 reported that soil C increased at a rate of emissions from switchgrass-based ethanol were 94% lower than estimated GHG emissions from gasoline. 41 In addition to increasing soil carbon (C), growing switchgrass may increase wildlife habitat, increase landscape and biological diversity, increase farm revenues, and return marginal farmland to production.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Frank et al 33 reported that soil C increased at a rate of emissions from switchgrass-based ethanol were 94% lower than estimated GHG emissions from gasoline. 41 In addition to increasing soil carbon (C), growing switchgrass may increase wildlife habitat, increase landscape and biological diversity, increase farm revenues, and return marginal farmland to production.…”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…In North Dakota, Frank et al 33 applied 67 kg N ha −1 in the autumn and harvested at the soil level for a 3-year average biomass yield of 6.4 and 9.1 Mg ha −1 for the upland cultivars Dacotah and Sunburst, respectively.…”
Section: Harvesting Switchgrass For Bioenergymentioning
confidence: 99%
“…Wu et al (2006) estimated that the net amount of CO 2 sequestered would be around 48.5 kg per dry metric ton of switchgrass. Frank et al (2004) examined Sunburst and Dacotah switchgrass cultivars and noted that the net system carbon gain doubled over a three-year period. Combined with the zero net carbon exchange as a result of burning bioethanol from switchgrass, addition of soil carbon results in the overall reduction of atmospheric release of CO 2 (Lynd et al, 1991).…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Perennial grasses such as switchgrass (Panicum virgatum L.) are known to sequester SOC [13][14][15][16][17], but the long-term effects of management practices such as N fertilization rate and harvest management on SOC sequestration by switchgrass are unknown. Perennial grasses could be used as bioenergy crops on about 20 million ha (ha010,000 m 2 ) of marginal or idle cropland in the USA alone [18].…”
Section: Introductionmentioning
confidence: 99%